Advanced modeling of lead-free piezocomposites: The role of nonlocal and nonlinear effects. (15th April 2020) - Krishnaswamy, Jagdish A.; Buroni, Federico C.; Melnik, Roderick; Rodriguez-Tembleque, Luis; Saez, Andres
Abstract: Lead-free piezocomposites are an ecofriendly route for sensing and harvesting energy from mechanical stimuli and it is important to develop accurate models which can capture essential physical processes underlying their performance. Current piezocomposite design heavily relies on the linear piezoelectric model which neglects nonlocal and nonlinear electro-elastic processes. Here we develop a more accurate modelling paradigm to determine the contributions from nonlocal flexoelectric and nonlinear electrostrictive effects towards the performance of lead-free piezocomposites. We find that in the case of microscale randomly shaped piezoelectric inclusions which represent a practical scenario, the flexoelectric effect does not contribute appreciably towards the piezoelectric response. However, the nonlinear electrostrictive effects impart significant strain-dependent responses. Further, in nano-modified composites, we find that the nonlinear electro-mechanical coupling can have different effects on the transverse and the longitudinal electro-elastic responses. In particular, the longitudinal electric field response, with the nonlinear contribution, is less sensitive to the polycrystalline structure of the piezoelectric inclusions. These observations clearly indicate that at larger strains, nonlinear effects cannot be neglected. In general, our results entail that it is important to include nonlocal and nonlinear processes for reliable and accurate modelling of piezocomposites.